2019
DOI: 10.7717/peerj.6353
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide characterization and expression analyses of the MYB superfamily genes during developmental stages in Chinese jujube

Abstract: The MYB transcription factor (TF) superfamily, one of the largest gene superfamilies, regulates a variety of physiological processes in plants. Although many MYB superfamily genes have been identified in plants, the MYB TFs in Chinese jujube (Ziziphus jujuba Mill.) have not been fully identified and characterized. Additionally, the functions of these genes remain unclear. In total, we identified 171 MYB superfamily genes in jujube and divided them into five subfamilies containing 99 genes of the R2R3-MYB subfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 76 publications
(146 reference statements)
3
25
0
Order By: Relevance
“…Recently, Wang et al [ 31 ] identified 108 R2R3-MYBs in chili pepper, five genes less than in our study, probably since our strategy for the identification and classification of CaMYBs was also based on the comparative analysis with other known MYB plant proteins. Consistent with our results, the R2R3-MYB subfamily has been reported as the largest subfamily of the MYB family in other plant species [ 15 , 17 , 46 ], with some exceptions [ 21 , 47 ]. The total number of CaMYB genes was higher than the number of MYB genes identified in Arabidopsis (198), tomato (127), and pineapple (184), but lower than those in potato (253), sunflower (245), and sesame (287) [ 17 , 18 , 19 , 20 , 21 , 47 ], suggesting a distinct degree of evolutionary expansion of the MYB family among plant species.…”
Section: Discussionsupporting
confidence: 92%
“…Recently, Wang et al [ 31 ] identified 108 R2R3-MYBs in chili pepper, five genes less than in our study, probably since our strategy for the identification and classification of CaMYBs was also based on the comparative analysis with other known MYB plant proteins. Consistent with our results, the R2R3-MYB subfamily has been reported as the largest subfamily of the MYB family in other plant species [ 15 , 17 , 46 ], with some exceptions [ 21 , 47 ]. The total number of CaMYB genes was higher than the number of MYB genes identified in Arabidopsis (198), tomato (127), and pineapple (184), but lower than those in potato (253), sunflower (245), and sesame (287) [ 17 , 18 , 19 , 20 , 21 , 47 ], suggesting a distinct degree of evolutionary expansion of the MYB family among plant species.…”
Section: Discussionsupporting
confidence: 92%
“…Abundant evidence in plants has confirmed the diverse roles of MYB genes in signal transduction, developmental regulation, biotic and abiotic stress responses, disease resistance, and secondary metabolism regulation Lee & Seo 2019;Qing et al 2019;Wu et al 2019b;He et al 2020;Ohno et al 2020). Similarly, a few studies have shown that MYB genes participate in stress response and developmental regulation in fungi (Valsecchi et al 2017;Wang et al 2018;.…”
Section: Introductionmentioning
confidence: 95%
“…Since the first identification of MYB genes from avian myeloblastosis virus ( Klempnauer et al 1982 ) and from plants ( Paz‐Ares et al 1987 ), the function of MYB genes has been widely studied. Abundant evidence in plants has confirmed the diverse roles of MYB genes in signal transduction, developmental regulation, biotic and abiotic stress responses, disease resistance, and secondary metabolism regulation ( An et al 2019 ; Lee & Seo 2019 ; Qing et al 2019 ; Wu et al 2019b ; He et al 2020 ; Ohno et al 2020 ). Similarly, a few studies have shown that MYB genes participate in stress response and developmental regulation in fungi ( Valsecchi et al 2017 ; Wang et al 2018 ; Li et al 2019 ).…”
mentioning
confidence: 99%
“…Each repeat includes about 50 amino acids, containing a series of highly conserved amino acid residues and interval sequences, wherein the amino acid residues participate in the binding process with DNA in the form of helix-turn-helix (HTH) [ 1 , 2 ]. MYB proteins can be divided into different classes according to the number of repeats: 1R-MYB (one repeats), R2R3-MYB (two repeats), R1R2R3-MYB (three repeats), and 4R-MYB (four repeats) [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%